Transcranial magnetic stimulation provides means to assess cortical plasticity and excitability in humans with fragile X syndrome and autism spectrum disorder - Oberman, Lindsay M.; Ifert-Miller, Frederick; Najib, Umer; Bashir, Shahid; Woollacott, Ione; Gonzalez-Heydrich, Joseph; Picker, Jonathan; Rotenberg, Alexander; Pascual-Leone, Alvaro (Frontiers in Synaptic Neuroscience, 2010)
Fragile X Syndrome (FXS) is the most common heritable cause of intellectual disability. In vitro electrophysiologic data from mouse models of FXS suggest that loss of fragile X mental retardation protein affects intracortical excitability and synaptic plasticity. Specifically, the cortex appears hyperexcitable, and use-dependent long-term potentiation (LTP) and long-term depression (LTD) of synaptic strength are abnormal. Though animal models provide important information, FXS and other neurodevelopmental disorders are human diseases and as such translational research to evaluate cortical excitability and plasticity must be applied in the human. Transcranial magnetic stimulation paradigms have recently been developed to non-invasively investigate cortical excitability using paired pulse stimulation, as well as LTP- and LTD-like synaptic plasticity in response to theta burst stimulation (TBS) in vivo in the human. TBS applied on consecutive days can be used to measure metaplasticity (the ability of the synapse to undergo a second plastic change following a recent induction of plasticity). The current study investigated intracortical inhibition, plasticity and metaplasticity in full mutation females with FXS, participants with autism spectrum disorders (ASD), and neurotypical controls. Results suggest that intracortical inhibition is normal in participants with FXS, while plasticity and metaplasticity appear abnormal. ASD participants showed abnormalities in plasticity and metaplasticity, as well as heterogeneity in intracortical inhibition. Our findings highlight the utility of non-invasive neurophysiological measures to translate insights from animal models to humans with neurodevelopmental disorders, and thus provide direct confirmation of cortical dysfunction in patients with FXS and ASD.